Pengaruh Penyajian Laporan Keuangan dan Aksesibilitas Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Desa dengan Transparansi Sebagai Variabel Intervening (Studi Pada Pemerintah Desa di Kabupaten Pati) (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the Effect of Financial Statement Presentation and Financial Report Accessibility on Village Financial Management Accountability with Transparency as an Intervening Variable. The population in this study is the financial manager at the Village Government in Pati Regency. The population in this study were village financial managers in 21 sub-districts in Pati Regency which consisted of 401 villages and the sample of this study was 45 villages or 356 respondents. The data collection method used is a questionnaire. Data analysis using path analysis. The results showed that the presentation of financial statements had a positive and significant effect on the Accountability of Village Financial Management in Pati Regency. Accessibility of Village Financial Reports has an influence on the Accountability of Village Financial Management in Pati Regency. Transparency has a significant effect on Village Financial Management Accountability. Transparency is able to mediate the relationship between the influence of Financial Statement Presentation on Village Financial Management Accountability. Transparency is able to mediate the relationship between the influence of Accessibility of Financial Statements on Accountability of Village Financial Management.